Análisis de la eficiencia y efectividad en los procesos de compras públicas: caso ESPAM MFL 2021-2023 - Alcívar Pazmiño, Yandri Fabricio (2025)
The objective of this research was to analyze the efficiency and effectiveness of the public procurement processes at ESPAM MFL during the period 2021–2023. For its development, induction, deduction, indicator analysis, and the 5W+1H method were used, complemented by techniques such as interviews, causal analysis, traffic light assessment, cause-effect matrix, and the 5W+1H matrix. The results obtained from the indicators of the National Public Procurement Service showed that contracting efficiency declined, shifting from a medium to a low performance in 2023, while effectiveness demonstrated sustained growth. Additionally, low effectiveness was identified in completed processes, as well as a decrease in the competitiveness of procurement processes through electronic auctions. If these results persist, they could negatively impact the execution of processes in subsequent years. Therefore, improvement actions are proposed to optimize procedures and enhance the administrative management of the Public Procurement Unit.